The current status and challenges of biomass biorefineries in Africa: A critical review and future perspectives for bioeconomy development - (:unkn) unknown (My University, 2023)
Africa benefits from diverse biomasses that are rich in high-added value materials and precursors for energy, food, agricultural, cosmetic and medicinal applications. Many African countries are interested in valorizing biomasses to develop efficient and integrated biorefinery processes and their use for local and regional economic development. Thus, this report critically reviews the current status of African biomass richness, its diversity, and potential applications. Moreover, particular attention is given to bioenergy production, mainly by biological and thermochemical conversion processes. This also includes biomass valorization in agriculture, particularly for the production of plant-based biostimulants, which are a potential emerging agri-input sector worldwide. This study points out that even though several processes for biofuel, biogas, biofertilizer and biostimulant production have already been established in Africa, their development on a larger scale remains limited. This study also reports the different socioeconomic and political aspects of biomass applications, along with their challenges, opportunities, and future research perspectives, to promote concrete technologies transferable into an industrial level.
Keywords: African Research